Teneurin-2 (TENM2) deficiency induces UCP1 expression in differentiating human fat cells. (5th March 2017) - Tews, D.; Fromme, T.; Keuper, M.; Hofmann, S.M.; Debatin, K.M.; Klingenspor, M.; Wabitsch, M.; Fischer-Posovszky, P.
Abstract: Under certain conditions UCP1 expressing adipocytes arise in white adipose tissue depots of both mice and humans. It is still not fully understood whether these cells differentiate de novo from specific progenitor cells or if they transdifferentiate from mature white adipocytes. Performing expression pattern analysis comparing adipocyte progenitor cells from deep and subcutaneous neck adipose tissue, we recently identified teneurin-2 (TENM2) enriched in white adipocyte progenitor cells. Here we tested whether TENM2 deficiency in adipocyte progenitor cells would lead to a brown adipocyte phenotype. By targeting TENM2 in SGBS preadipocytes using siRNA, we demonstrate that TENM2 knockdown induces both UCP1 mRNA and protein expression upon adipogenic differentiation without affecting mitochondrial mass. Furthermore, TENM2 knockdown in human SGBS adipocytes resulted in increased basal and leak mitochondrial respiration. In line with our previous observation these data suggest that TENM2 deficiency in human adipocyte precursors leads to induction of brown adipocyte marker genes upon adipogenic differentiation. Highlights: TENM2 is higher expressed in human white compared to brown preadipocytes. TENM2 deficiency in human preadipocytes leads to upregulation of UCP1 expression. This in turn results in increased basal and leak respiration rates.